The problem of social inequality in the USA - N. E. Petrovskaya (Вестник университета)
The article explores the problem of social inequality in modern American society. The author draws attention to various aspects of this phenomenon, including economic inequality in terms of income, wealth, access to education and health care, age, racial-ethnic and gender aspects. In the USA the social in-equality level is one of the highest in the world. The article cites statistics and scientific papers that demonstrate the growing gulf between the rich and the poor. It also emphasizes how racial and gender discrimination affects social inequality, preventing individuals from realizing their full potential. The problem of social stratification has been shown. The article also focuses on the poverty rate and the phenomenon of the working poor. The author gives an illustration of social inequality by cities and states. Social inequality in the USA has a long history and an increasing trend, i.e. it is a chronic social inequality. General scientific methods, systemic and complex approaches were used. The article presents an overview of social inequality problem in the USA and suggests ways of its solution. It emphasizes the need for an integrated approach and cooperation between different population groups to achieve a more just and equitable society.